Antibodies to Shiga toxins in Brazilian cattle. (July 2017) - Yamamoto, Bruno B.; Luz, Daniela; Abreu, Patrícia A.E.; Gotti, Tatiana B.; Vasconcellos, Silvio A.; Piazza, Roxane M.F.; Horton, Denise S.P.Q.
Abstract: Cattle are considered a reservoir of Shiga toxin-producing Escherichia coli (STEC). There is no information about the presence of antibodies against Shiga toxins in Brazilian bovine serum. Using ELISA, all sera tested showed antibodies against the two main STEC virulence factors; Stx1 and Stx2. Neutralizing antibodies against Stx1 and/or Stx2 were detected in all but one serum. In conclusion, our results indicated that these animals had been exposed to STEC producing both toxins. Highlights: Brazilian bovine sera presented antibodies titers against Stx1 and Stx2. All, but one sera presented antibodies with neutralizing ability. Brazilian cattle have been exposed to STEC producing both toxins.